Masa Depan Peragaan Busana yang Terinspirasi oleh Biomimikri Rafflesia Rhizanthes Deceptor dalam Virtual Reality: Pendekatan Lintas Platform untuk Desain Fesyen Digital dan Simulasi VR yang Imersif - Qatrunnada, Kimberlita; Mutiaz, Intan Rizky (Jurnal Bahasa Rupa, 2025)
The phenomenon of digital fashion is undergoing a significant transformation in the global fashion industry, driven by internet advancements and a shift towards digital experiences as a hallmark of the Fashion 4.0 era. This research employs the Double Diamond methodology with a focus on visual exploration, applying biomimicry inspired by the morphology of the Rafflesia Rhizanthes Deceptor flower. Its aim is to formulate contextual visual strategies for introducing this flower to Generation Z through a virtual fashion show based on Virtual Reality (VR). The digital design process involved detailed modeling of garments and accessories using CLO 3D and Blender, subsequently realized within the Unreal Engine environment. VR revolutionizes audience interaction with fashion through immersive visual narratives. In this virtual space, elements such as light direction, color contrast, and animation serve as a semiotic system to guide audience perception. Although VR offers 360° viewpoint flexibility, designers strategically direct audience focus using dominant visual cues. Overall, this research contributes to the development of nature-inspired digital fashion design and the construction of imaginative visual narratives that align with immersive media, opening new opportunities for the fashion industry within the rapidly evolving digital landscape.